(untitled) (TEST Ticontre. Theory Text Translation, 2026)
Contemporary Korean-German philosopher Byung-Chul Han developed in recent years a severe and harsh analysis of digital technologies, critically assessing them in their essence and their mass application, which causes profoundly negative psycho-social behaviors. In particular, Han’s discourse focuses on the idea of loss of the world; in fact, the digital cancels all contact with reality and things, nullifying the relationship with material physicality, with its weight, body and contrasting consistency. The article intends to analyze the significant presence of the great 20th century modernist literature (especially Kafka, Musil, Proust) and coeval thought (W. Benjamin) in Han’s works. Modernist works pose some fundamental questions, starting from the unknowability of the world and his unwillingness to a quick and certain decoding. These elements, which the modernists interpret as problematic and negative, become, when viewed through a contemporary lens instead, full of a partly positive and significant value. Hence, Han develops an interpretation of modernism in which things have, on the one hand, a resistant charge together with an alienating presence, and, on the other, a epiphanic and auratic power. Ultimately, modernism becomes an initiatory and contemplative ideal opposed to the practical triviality of digital society.